Immune infiltration in aggressive papillary craniopharyngioma: High infiltration but low action - Jia, Yanfei; Ma, Lin; Cai, Kefan; Zhang, Bochao; Wu, Wentao; Xiao, Youchao; Qiao, Ning; Ru, Siming; Cao, Lei; Gao, Hua; Gui, Songbai (Frontiers in Immunology, 2022)
Papillary craniopharyngiomas (PCPs) are biologically benign but clinically aggressive lesions hence affect the quality of life. The expression of inflammatory mediators and regulation of the immune microenvironment in PCPs have not been investigated much. In this study, for the first time, we assessed the immune cell infiltration and immune cell signatures in PCPs by analyzing the bulk-RNA sequencing data and immunohistochemical staining. Additionally, we performed qRT-PCR analysis to detect inflammatory mediators interleukin-1α (IL1A) and interleukin-6 (IL6) in different aggressive groups and then developed the IL1A and IL6 prediction models for defining the degree of hypothalamic invasion. Lastly, we defined differentially expressed genes related to invasiveness and implemented enrichment analysis to them. Our results indicated that PCPs are in a state of high immune infiltration but low action with abundant inflammatory cells. High infiltration of neutrophils may lead a low active immune microenvironment. Furthermore, the high expression level of IL1A and IL6 was positively correlated with the invasion of PCP tumors in the hypothalamus. These findings provide new pathological insights into the underlying mechanism of the immune microenvironment in PCP tumors. Moreover, IL1A and IL6 might serve as potential therapeutic targets for PCP tumors, especially to prevent their invasion into the hypothalamus.